Uji Aktivitas Produk Sediaan lipgloss dari buah kesumba keling (Bixa orellana L) sebagai pewarna alami - Christica Ilsanna Surbakti; Artha Yuliana Sianipar; Cut Masyitah Thaib (Journal of Pharmaceutical and Sciences, 2023)
The general of kesumba keling fruit is one of the potential plants as natural dyes.Moreover,kesumba keling fruit also useful for diuretic,antipiretic,and neutralizing toxins in the body.One of the plants that can be made in lip coloring is kesumba keling fruit one of the most used cosmetic product is lipgloss..lipgloss in using be easy to apply and give a shiny impression.The purpose of this research is to know if kesumba keling fruit skin extract can be used as natural dye substitute for synthetic dyes on lipid dye preparations.On day 1 to 30 color prepararion on change.Lipgloss with consentration of kesumba keling 10% light yellow,12% giving dark yellow,14% consentration giving a reddish yellow color.Lipgloss preparation is the distinctive smell of kesumba keling fruit extract that is most preffered by panelist with concentration of 12%,because the preparation of lipgloss from kesumba keling fruit extract doesn’t cause irritation.Conclusions : Point out the difference between icreasing concentration of the kesumba celing fruit extract to used in formula then the more consentrated color of the lipgloss produced increased.Lipgloss with 10% concentration are light yellow,lipgloss preparation with 12% concentrated are dark yellow,lipgloss preparation with 14% conceration are reddish yellow and on days1 to 30 preparation on change.